Combined effects of low temperature nitriding and cold rolling on fatigue properties of commercially pure titanium. (October 2020) - Kikuchi, Shoichi; Ueno, Akira; Akebono, Hiroyuki
Highlights: Nitrogen diffusion is observed on the surface of CP titanium nitrided at 773 K. A nitrogen compound layer is formed on the surface of CP titanium nitrided at 823 K. Low temperature nitriding prevents the reduction of fatigue limit of CP titanium. Low temperature nitriding at 873 K decreases the friction coefficient of CP titanium. Low temperature nitriding at 873 K reduces the wear loss of CP titanium. Abstract: The combined effects of low-temperature nitriding (LTN) and cold rolling on the microstructure of commercially pure titanium (CP titanium) were investigated. The grain size of the LTN-treated CP titanium decreased with increasing thickness reduction due to the cold rolling pre-treatment and with decreasing the nitriding temperature. The fatigue limit for the nitrided CP titanium depended on the grain size beneath the nitrided layer and increased with decreasing the nitriding temperature because of the suppression of grain-coarsening. Furthermore, the LTN at 873 K decreased the friction coefficient and reduced the wear loss of CP titanium during the ball-on-disk dry friction tests.